Research on the Rock Pressure Behavior at Close-Distance Island Working Faces under Deep Goaf - Shoulong Ma (Advances in Civil Engineering)
In order to realize the safe and efficient mining of the short-distance isolated island working face under the deep goaf area, the 120502 isolated island working face of Liuzhuang Mine was taken as the engineering background. The method of combining numerical simulation and field measurement were used comprehensively to systematically simulate and study the spatial evolution of the stress field, plastic strain field, and fracture field of coal rock during the mining process. The leading support pressure and the vertical displacement of the roof in the overlapping section and noncoinciding section of the isolated working face and the goaf above were measured on site. The results are that the peak value of the advanced support pressure of the overlap section and the nonoverlapping section is 10 m before the coal wall of the working face; the advanced support pressure of the nonoverlapping section is 33.3 MPa, and the vertical displacement of the roof is 300 mm. The advanced support pressure and the vertical displacement of the roof in the noncoincidence section were significantly higher than those in the coincidence section of 18.2 MPa and 210 mm. The results are consistent with those predicted by numerical simulation. This provides theoretical support for the safe mining of the 120502 isolated island working face in Liuzhuang Mine and, at the same time, provides a reference for the study of similar working faces in other domestic mining areas.